Diseño y desarrollo de un ambientador líquido a partir del aceite esencial de Palo Santo (Bursera graveolens) - Jaramillo Gutiérrez, Patricia Katherine (2014)
In the present study, a liquid air freshener as the active ingredient using the essential oil of Palo Santo (Bursera graveolens) was developed. Studies were conducted of preformulation as the valuation of the essential oil by means of gas chromatography coupled to mass spectrometry (GC/MS), where it was noted that the major components of the oil were limonene (59.84 %) and α-phellandrene (24.66 %). He also did studies of formulation based on the factorial design of and Plackett Burman, in order to determine the compatibility between active principle - excipients and select the final mix, which will be subjected to stability studies. (Six months). The study of physico-chemical parameters such as pH, density and concentration of the active ingredient was performed. He also conducted the study against microbiological parameters: aerobic mesophilic bacteria, molds, fungi and yeasts, showing growth inhibition during the six-month stability study Finally he could not determine the prediction of the lifetime of the liquid air freshener by the method of Arrhenius.